Epidemiological studies of black pepper anthracnose (Colletotrichum gloeosporioides) - BIJU, C N; PRAVEENA, R; ANKEGOWDA, S J; DARSHANA, C N; JASHMI, K C (The Indian Journal of Agricultural Sciences, 2026)
Black pepper (Piper nigrum L.) occupies a unique position in the spice industry. Anthracnose or fungal pollu incited by Colletotrichum gloeosporioides (Penz.) Penz. and Sacc. is a wide spread and economically important disease of black pepper. The influence of weather factors such as temperature, rainfall and number of rainy days was studied by correlating the disease incidence during different months vis-a-vis weather parameters. The results indicated that, maximum temperature has negative correlation, while minimum temperature, rainfall and number of rainy days have positive correlation with the disease incidence. Newly emerged leaves on the runner shoots, orthotrophs and plagiotrophs as well as young spikes were found to be more vulnerable to the disease.